Knowledge for development: Local and external knowledge in development research - Caleb Wall (University of Bonn, Center for Development Research (ZEF), 2006)
The contribution that science and technology can make to development is well understood - but for new 'knowledge' to have an impact it must connect with existing local knowledge. Presented in this essay is a discussion of how development research projects can make a positive contribution to development, through the use of new science and technology - coupled with local knowledge. Drawing on field research conducted in rural Uzbekistan, under the aegis of a natural science driven project, I reflect here on the meaning of 'development research' and make a case for combining external scientific research with practical development interventions. Specifically, through the use of participatory methods, accepting that development research is a process. This is argued both as academically challenging and interesting as well as ethically necessary for projects choosing to work in the developing world. I discuss my experiences in learning from local knowledge, outlining the principals of affording dignity to local partners, respecting local knowledge and experts, understanding the cultural context of knowledge and maintaining a constant willingness to learn. With these principals I present how it is possible to work in a collaborative manner towards developing locally appropriate and accessible technologies, and the importance of doing so in a sustainable manner.
urn:nbn:de:0202-20080911120
Keywords: 330